Unsur-Unsur Perjanjian yang Tidak Terpenuhi (Studi Kasus Wanprestasi antara PT Garuda Metro Batavia dengan PT Garuda Maintenance Facility (GMF) - Qiana, Qayla Khansa; Putri, Nabila Aulia Adek; Maharani, Nabilah Liztha; Salma, Athifa Huurun (UNIVERSITAS SERAMBI MEKKAH, 2025)
Bond Law is the law that regulates the legal relationship between parties involved in an agreement, where each party has rights and obligations that must be fulfilled. Non-fulfilment of essential elements, such as agreement and freedom of contract, can result in default, the legal consequences that arise, as well as dispute resolution mechanisms that can be taken by the injured party. Meanwhile, default can occur in various forms, ranging from not carrying out obligations according to the specified time, not fulfilling the agreed quality or quantity, to taking actions that are contrary to the agreement. In this case, an agreement that is not fulfilled properly can have serious legal consequences, either in the form of compensation or cancellation of the agreement.